EPISTEMOLOGI BAYANI - Soleh, A. Khudori (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
Bayani is a typical Arab epicurean based on the text. According to him, the source of knowledge is the text, which in the religious perspective is the Koran and the Hadith. How to get knowledge through earnest: (1) based on the editorial composition of the text being studied through lingistic analysis, (2) based on the qiyas or ambgi method seen from one of three aspects, namely the relationship between ashl and far ', ilbt which is on ashl and far ', and the tendency that unites ashl and far'. In its development, the Bayan Anabgi is not only used to explore the knowledge of the text, but also used to understand the reality of non-physical conditions and to logically interpret physical reality (qiyas al ghaib ‘ala al syahid). Among other things, about metaphysical theories and theological doctrines. Because it is only based on the text, bayani thinking becomes